Dasatinib‐induced chylothorax: An unusual presentation of a common adverse event—A case report with literature review - Theresa Paul (13140759) (2023)
Tyrosine kinase inhibitors (TKIs) are the key agents for treating CML and BCR–ABL+ B-ALL. Dasatinib is a potent second-generation TKI. Here, we have discussed the case of a 51-year-old gentleman diagnosed with B-myeloid mixed-phenotype acute leukemia with t(9;22)(q34.1;q11.2); BCR–ABL1p210, in complete hematological, cytogenetic, and molecular remission, who developed chylothorax. Though pleural effusion is a commonly observed adverse effect of dasatinib therapy, chylothorax is rare. The ability of Dasatinib to inhibit multiple families of tyrosine kinases could be considered the etiology. Discontinuation of the drug resolved the symptom, but pleural effusion recurred once Dasatinib was resumed. Chylothorax induced by Dasatinib is a differential to be kept in mind, owing to the limited number of cases being reported. Other Information Published in: eJHaem License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/jha2.226